Conjugated linoleic acid reduces permeability and fluidity of adipose plasma membranes from obese Zucker rats - Martins, Ana Paula (2013)
NOTICE: this is the author’s version of a work that was accepted for publication in Biochemical and Biophysical Research Communications. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Biochemical and Biophysical Research Communications. July 2010; 398 (2): 199-204.